The REVAMP trial to evaluate HIV resistance testing in sub-Saharan Africa: a case study in clinical trial design in resource limited settings to optimize effectiveness and cost effectiveness estimates. Issue 4 (4th July 2017) - Siedner, Mark J.; Bwana, Mwebesa B.; Moosa, Mahomed-Yunus S.; Paul, Michelle; Pillay, Selvan; McCluskey, Suzanne; Aturinda, Isaac; Ard, Kevin; Muyindike, Winnie; Moodley, Pravikrishnen; Brijkumar, Jaysingh; Rautenberg, Tamlyn; et al.
Abstract : Background: In sub-Saharan Africa, rates of sustained HIV virologic suppression remain below international goals. HIV resistance testing, while common in resource-rich settings, has not gained traction due to concerns about cost and sustainability. Objective: We designed a randomized clinical trial to determine the feasibility, effectiveness, and cost-effectiveness of routine HIV resistance testing in sub-Saharan Africa. Approach: We describe challenges common to intervention studies in resource-limited settings, and strategies used to address them, including: (1) optimizing generalizability and cost-effectiveness estimates to promote transition from study results to policy; (2) minimizing bias due to patient attrition; and (3) addressing ethical issues related to enrollment of pregnant women. Methods: The study randomizes people in Uganda and South Africa with virologic failure on first-line therapy to standard of care virologic monitoring or immediate resistance testing. To strengthen external validity, study procedures are conducted within publicly supported laboratory and clinical facilities using local staff. To optimize cost estimates, we collect primary data on quality of life and medical resource utilization. To minimize losses from observation, we collect locally relevant contact information, including Whatsapp account details, for field-based tracking of missing participants. Finally, pregnant women are followed with an adapted protocol which includes an increased visit frequency to minimize risk to them and their fetuses. Conclusions: REVAMP is a pragammatic randomized clinical trial designed to test the effectiveness and cost-effectiveness of HIV resistance testing versus standard of care in sub-Saharan Africa. We anticipate the results will directly inform HIV policy in sub-Saharan Africa to optimize care for HIV-infected patients.